The internet of things in high andean wetland monitoring, historical review approach - Vladimir Henao-Céspedes; Gloria Yaneth Florez; Yeison Alberto Garcés-Gómez (Institute of Advanced Engineering and Science, 2021)
The internet of things (IoT) has allowed important technological advances for monitoring and telemetry, thanks to the fact that IoT-based systems allow to obtain information in large areas, far from urban environments, and where low energy monitoring systems are required, features that are consistent with the requirements for high Andean wetlands telemetry. The monitoring of environmental variables, such as water quality in high Andean wetlands, is a topic of great importance for the scientific community, since, if the knowledge of the dynamics of the wetlands is improved, it is possible to optimize the decision making for their conservation. In that sense, to know the application of the IoT in this type of wetlands at a global level, this work presents a review of the literature related to the use of the IoT in the monitoring of high Andean wetlands. In order to carry out a historical review, a methodology was proposed under some guiding questions, which allowed designing a structure for background searches. Both the questions and the structure guided the search process from macro areas, such as IoT and environment, to micro areas, such as IoT applications in wetland monitoring. Finally, the review concluded that IoT has not been applied in high Andean wetland monitoring.